PENGARUH PAD DAN DAU TERHADAP BELANJA DAERAH PADA KABUPATEN/KOTA JAWA TIMUR - Apriliawati, Kiki Ninda; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine whether the PAD and the DAU has influence to the local expenditure in the Districts / Cities Government in East Java Province and to analyze the possibility of the occurrence of flypaper effect to the Local Expenditure in the Districts / Cities Government in East Java Province in 2012-2014 periods. The population is all districts / cities in the area of East Java Province. The data employs the secondary data which has been obtained from the Budget Realization Statement of Districts / Cities in East Java Province from 2012 to 2014 which have been obtained from the Audit Board of the Republic of Indonesia (BPK. RI). The representatives from East Java province is in the form of the Result of Financial Audit Report of Districts / Cities in East Java Province. The data analysis instrument which has been employed in this research is the multiple linear analyses. Based on the result of the test, it shows that: 1) the Local Own Source Revenue has positive influence to the Local Expenditure in the districts / cities government in East Java Province; 2) The General Allocation Fund has positive influence to the Local Expenditure in the districts / cities government in East Java Province; 3) The flypaper effect has occurred in the districts / cities government in East Java Province.Keywords: Local Own Source Revenue (PAD), General Allocation Fund (DAU), Flypaper Effect.